The Concept of Sharī‘a Revisited - Ali, Ali A Rahim (Journal of Islamic Thought and Civilization, 2023)
Sharī‘a is considered as a central concept in Islam. The wide range of Islamic aspects covered by this term has led some scholars to argue that Sharī‘a and Islam have become synonymous terms. The terminological obscurity is further increased by the dual nature of Sharī‘a, where divine and mundane dimensions are both present. Moreover, the implications of this obscurity are observable in the ongoing debates about the changeability of Sharī‘a. Therefore, the current study attempted to demystify how a central concept in Islam, such as Sharī‘a, is so vaguely defined. It also examined different factors that contributed to this vagueness, for instance, terminology, history, and politics. However, the focus of the study remained most importantly on the dual nature of Sharī‘a, stemming from a desideratum for divinity and the inevitability of human agency. This obscurity has practical implications, for instance, the classification of banks' interest as riba (usury). However, a more general implication is the degree of flexibility in Sharī‘a, since changeability is proportional to the degree of divinity. Muslims need to have a clearer idea of what Sharī‘a is, to have substantial relevance in modern times.